Opinions on Raising Finishing Pigs of Smallholder Farmers at Mueang Nakhon Si Thammarat District in Nakhon Si Thammarat Province - Somphon Noppakeua; Yenying Chongchit (My University, 2021)
The research aimed to study: 1) general information of smallholder farmers and finishing pig raising conditions, 2) opinions of the farmers on raising finishing pigs at Mueang District, Nakhon Si Thammarat Province. The research population was a group of 172 finishing pig farmers at Mueang District, Nakhon Si Thammarat Province. The sample of 120 were selected using a multistage sampling formula in which reliability and validity assessed questionnaires were used. The results showed that 55% of the samples are female farmers approximately aged 58 years old, with primary education, raising pigs as the main career with an average monthly income at 23,588 Baht and average monthly farming expense at 11,599 Baht. The opinions in descending order were farming area (=4.67), distribution and returns (=4.35), current raising conditions ( =4.17), sustainability ( =3.71), feed management and sanitation ( =3.08), farming equipment ( =2.87), funding ( =2.09), and government service ( =1.42). These indicate that farming areas have highly positive opinion because of adequate utility and good quality of drinking water resources and relatively high on the distribution and returns as it is a major household income. The funding has a low score because of inadequate funding and the government service needs an improvement. In conclusion, this research will be used as a further guideline for government and private sectors to promote the raised of finishing pigs.
Keywords: Livestock Farming and Management